The Effect of Financial Literacy on Cryptocurrency Investment Intention: The Mediating Role of Perceived Risk - Vidya Ramadhan Putra Pratama (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the effect of financial literacy on cryptocurrency investment intention and tests whether perceived risk mediates the relationship. A quantitative cross-sectional survey was conducted among 40 active cryptocurrency investors in Indonesia. The model was estimated using variance-based Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.29. The measurement model satisfied reliability, convergent validity, and discriminant validity requirements. The structural model shows that financial literacy has a positive and significant effect on investment intention (β = 0.700; p < 0.001) and, unexpectedly, also has a positive and significant effect on perceived risk (β = 0.703; p < 0.001). Perceived risk does not significantly affect investment intention (β = 0.003; p = 0.495), and the indirect effect of financial literacy through perceived risk is insignificant (β = 0.002; p = 0.495). These findings indicate that financially literate crypto investors may recognize more risks without becoming less willing to invest. Accordingly, financial literacy may operate primarily as a decision-enabling and risk-recognition capability rather than through a risk-reduction mechanism. The study contributes to the literature by distinguishing risk awareness from risk avoidance among active cryptocurrency investors and highlights the need for investor education that emphasizes risk-management competence.